P48 Modifying health promotion interventions for ethnic minority groups: systematic overview of guidelines and reviews. (16th November 2010) - Davidson, E; Liu, J J; Yousuf, U; Bhopal, R; Johnson, M; White, M; Netto, G; Deverill, M; Sheikh, A
Abstract : Background: Some UK ethnic minority groups experience disproportionate levels of morbidity and mortality when compared with the majority White population. For these populations, access to and use of health promotion interventions may be limited. Adaptation of smoking cessation, physical activity and nutrition interventions of proven effectiveness for the majority population could represent an efficient strategy for reducing persistent health inequalities when adapted for minority ethnic populations. Objectives: To identify the high-level evidence for health promotion interventions which have proven effectiveness for the general population and construct a framework of effective interventions, including any recommendations relating to ethnic minority populations. Design: A systematic overview was conducted with two reviewers independently searching and identifying guidelines and systematic reviews of interventions for smoking cessation, improving nutrition and physical activity. SIGN, NICE and Clinical Evidence databases were searched for relevant guidelines. Cochrane Library, Campbell Collection, HTA reviews and DARE databases were searched for systematic reviews. Data on the effectiveness of interventions were extracted. Results: 19 guidelines were identified as relevant. 2399 systematic review records were identified and assessed for eligibility. 187 systematic reviews were included in the final analysis. The guidelines revealed a large evidence base for smoking cessation interventions, but highlighted major gaps in relation to how best to increase physical activity and improve nutrition. There was little advice in these guidelines on how to adapt interventions to meet the needs of ethnic minority populations. The 187 systematic reviews were screened to identify any additional effective interventions not included in the guidelines. All effective, evidence-based interventions have been compiled into a summary framework. The 187 systematic reviews were also subjected to a detailed assessment of the population composition to determine whether any subgroup analysis for ethnic minority groups was undertaken. Approximately half of the reviews reported the inclusion of ethnic minority groups; however, no reviews conducted subgroup analyses according to ethnicity and ethnic-specific recommendations were scarce. Conclusions: The evidence base reviewed provides specific guidance on effective interventions for smoking cessation, but generic advice for increasing physical activity and improving nutrition. Identification of the range of evidence-based interventions for these three areas has led to the development of a summary framework that can be utilised for health promotion. Interventions already found to be effective in the majority population are, if appropriately adapted, likely to prove effective in minority ethnic populations. This work will advance current guidance on how to approach adaptation.